Mechanisms Underlying the Development of the Modern Family Image - Rustamovna, Mirzayeva Sayyora (Jurnal Psikologi, 2025)
The following article analyzes the issues of the formation and development of the image of the modern family. The social role of the family institute is considered, its transformation under the influence of various cultural, economic and political factors. In modern society, the processes of family self-image, family relationships and change in values are discussed. Also, the main trends in the formation of the image of the family are revealed as a result of the influence of globalization, digital technologies, gender equality and new family norms. Meanwhile, the article discusses the importance of the family in society, its roles and the evolution of family relationships, as well as stereotypes about the modern family. By creating an image of the family in different social groups, the author calls for a revision of concepts about the family in society in a new, modern context.